Assessment of cow and farm level risk factors associated with Ureaplasma diversum in pasture-based dairy systems - A field study - NASCIMENTO-ROCHA,JOSEFA M. (2017)
ABSTRACT Potential risk factors for Ureaplasma diversum in the vaginal mucus of 1,238 dairy cows were included in a multivariate logistic regression model, based on the cow level (i.e., granular vulvovaginitis [+GVV], yearly milk production [4500 kg or more], pregnancy, predominance of Bos taurus [+Bos Taurus], score of corporal condition [at least 2.5], concomitant positivity for Escherichia coli [+E.coli]), and farm level i.e., milking room hygiene (-Milking room), dunghill location, and replacement female). Ureaplasma diversum was present in 41.1% of the samples. Independent risk factors for U. diversum were +GVV (odds ratio [OR], 1.31); +Mycoplasma spp (OR, 5.67); yearly milk production (4500 kg or more) (OR, 1.99); +Bos taurus (OR, 1.68); +E. coli (OR, 4.96); -milking room (OR, 2.31); and replacement females (OR, 1.89). Ureaplasma diversum vaginal colonization was strongly associated with Mycoplasma spp., E. coli, and number of pregnant cows.